PELAKSANAAN BAURAN PROMOSI PAKET WISATA DI PT. URBANITAS TOUR AND TRAVEL PEKANBARU RIAU - Muhammad Faisal; Andi M. Rifiyan Arief (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The purpose of this study is to defermine how the implementation mix promotion package at PT. Urbanity Tour and Travel Pekanbaru Riau.The study was used qualitative metodhe with descriptif approach to describe the real condition by collecting the information data in the field. The informan keys in the study were 1 chief excecutive officer and 3 other employees at PT. Urbanity Tour and Travel Pekanbaru Riau. The technique collecting the data in the study used interview, vation and documentation.Based on the result of the study, it is determined that mix promotion conducted in PT. Urbanity Tour and Travel Pekanbaru Riau are advertising via printed media such as newspaper and banner, website media, Personal selling Comonication directly with certain customers, Sales Promotion by giving kickers, Public relation sponsore some events, words of mouth consumers to consumers, Direct marketing using direct contacts, telephones and emails.Key Words : Mix Promotion, Tour Packaget PT. Urbanity Tour and Travel Pekanbaru Riau